Germany in fundamental macroeconomic disequilibrium: The external surplus - Jan Priewe (Hans-Böckler-Stiftung, Macroeconomic Policy Institute (IMK), Forum for Macroeconomics and Macroeconomic Policies (FMM), 2018)
Despite performing very positively on some key macroeconomic indicators in recent years, the German economy is in grave disequilibrium if the high current account surplus is included in the analysis. The paper scrutinises the evolution of Germany's external surplus since the inception of the Euro in 1999. This is done by identifying the main determinants of exports and imports and by analysing the accounting identity in which the current account is national saving less total fixed investment. While price competitiveness measured by real exchange rates is strongly improved by German imports for exports within international value chains, also by real undervaluation against other member countries, the focus is on the combination of price- and non-price competitiveness. The latter is mainly determined by the global income elasticity for imports from Germany, relative to the income elasticity for imports to Germany. Despite heavy fluctuations, the past trend shows a clear wedge between the growth of exports and imports of almost one percentage point. If this trend continues the German trade balance would reach 15% of GDP in 2026 which would be a time bomb for the cohesion of the European Monetary Union. Market-based rebalancing is not in sight. It is the built-in dynamics of the external surplus that is hazardous. The problem is aggravated as Germany sits in the same boat with three other hard-core surplus seeking countries (Netherlands, Ireland, Luxembourg). In recent years the imbalances within EMU have changed, pulling former deficit countries in mild surplus but leaving the diversity of current account balances among EMU members at a spread of 8-10 percentage points, with an external trade surplus of EMU as a whole of 4.5% and 3.5% current account surplus. Germany carries nearly 77% and 55% of the current account and the trade surplus, respectively, and has - far ahead others - become the largest surplus country on the globe, in absolute terms. This constellation is unsustainable and requires policy action in Germany, in the European Union, the Euro Area and also by global authorities.
Keywords: E5; E6; F14; F15; F41; F42; F45; 330; balance of payments; global imbalances; real exchange rates; competitiveness; European Monetary Union